2000
DOI: 10.1159/000023507
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactinemia in Childhood and Adolescence: A Cause of Asymptomatic Hyperprolactinemia

Abstract: Asymptomatic hyperprolactinemias associated with altered proportions of molecular forms of circulating prolactin (PRL) have been reported in adults. The scarce references available in children and adolescents prompted us to report our experience in the evaluation and follow-up of patients with macroprolactinemia. We studied 5 patients (1 male and 4 females) aged 11.6–18 years with incidentally discovered asymptomatic hyperprolactinemia. Patients underwent repeated evaluations for a period of 3 months to 8 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 16 publications
2
23
0
11
Order By: Relevance
“…Although subjects in this study may be too old to determine when macroprolactinaemia began, the current data suggest that macroprolactinaemia is likely to begin before middle age. This assumption is supported by a few reports that demonstrated the presence of macroprolactinaemia in childhood and adolescence (19,20,21).…”
Section: Discussionmentioning
confidence: 54%
“…Although subjects in this study may be too old to determine when macroprolactinaemia began, the current data suggest that macroprolactinaemia is likely to begin before middle age. This assumption is supported by a few reports that demonstrated the presence of macroprolactinaemia in childhood and adolescence (19,20,21).…”
Section: Discussionmentioning
confidence: 54%
“…Hyperprolactinemia in children has been described in association with other conditions such as hypothyroidism [4] and celiac disease [5], or with the presence of macroprolactin [6]. These conditions were excluded in our patient.…”
mentioning
confidence: 99%
“…Fideleff et al reported 5 asymptomatic cases with macroprolactinemia that was a casual finding. Above all, 2 of their cases were detected during a study they performed on 304 healthy children and adolescents to establish reference values for prolactin [10]. More recently, Tütüncüler et al presented 6 children with macroprolactinemia, of whom 5 had manifestations consistent with endocrinopathy (headaches, menstrual disturbance, short stature, increased hair and early puberty).…”
Section: Discussionmentioning
confidence: 99%